Correlation and the omitted variable: A tale of two prices. Issue 2 (22nd September 2020) - Han, Xing; Pan, Zheyao
Abstract: We offer a new perspective on the low‐beta anomaly by acknowledging the omitted‐variable problem in the correlation component of beta: Correlation is "plagued" by firm size (the omitted variable) to exhibit a negative price. Once isolating the size impact, a hidden positive price emerges for the size‐orthogonalized component of correlation. Further analyses suggest that (a) the positive price of the size‐orthogonalized component is not due to mispricing, supporting the return comovement‐based pricing channel; (b) the negative price of the size‐explained component is related to illiquidity and coskewness.; (c) the omitted‐variable problem also applies to the pricing of beta.